(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To determine the rate of COVID-19 vaccine booster shot (BS) and assess the factors influencing the vaccination decision of people in Tan Chau commune, Di Linh district, Lam Dong province. Methods: A cross-sectional descriptive study was conducted on 360 people aged 18 and over in Tan Chau Commune, Di Linh District, Lam Dong Province. Data was collected by direct interview of the study subjects using a pre-prepared questionnaire and the 5C psychological premise scale affecting the vaccination decision. Results: The rate of COVID-19 vaccine BS among the study participants was high, at 84.7%, of which 39.4% had received the third dose and 35.3% had received the fourth dose. The K’Ho ethnic group had a lower BS rate than the Kinh ethnic group. The participant group with higher education had a higher BS rate. All sub-scales of the 5C scale had a sigificant impact on the COVID-19 vaccine booster rate. Conclusion: It is necessary to increase access, promote the importance and benefits of COVID-19 vaccine booster shots, and focus on the K’Ho ethnic minority, and people with low education levels. Raise the level of confident in vaccines, responsibility to the community in preventing the spread of the epidemic; emphasize the danger of the epidemic, remove barriers in accessing vaccination to increase the rate of COVID-19 vaccine BS.